PENGGUNAAN MEDIA TRADISIONAL ENGKLEK DALAM MENINGKATKAN KEMAMPUAN MEMBACA SISWA DI SD NEGERI LANGGA KABUPATEN PIDIE - Evi Zuhara (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2023)
Reading is a form of student skill in the form of the ability to recognize letters, the ability to spell words or sentences, reading fluency, understanding punctuation, being able to retell the contents of the reading, and having a business to obtain reading sources. Students who have reading difficulties will find it difficult to understand the lesson, students tend to have low academic achievement because of the reading difficulties they experience. The aim of the study was to find out how the use of the crank in overcoming students' reading difficulties at SD Negeri Langga. This type of research is quantitative research using experimental methods with One Group Pretest-Postest Design. The research sample is 8 students. Data collection techniques in this study used a Likert scale by distributing questionnaires to students in grades IV, V, and VI of SD Negeri Langga. The results showed that the use of cranks had significance in overcoming students' reading difficulties which was marked by a change in the average pretest score of 35.50 to 52.50 in the posttest average score with the difference between the two being 17. That is, there was an increase in students' reading ability after using a crank. The conclusion of the research shows that the crank can be used as a medium to improve students' reading skills, so this research can be used as reference material for class teachers and subject teachers in preparing programs for using the crank as a medium in improving students' reading skills.